2014
DOI: 10.1167/iovs.14-14126
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes in Heparan Sulfate in Human Bruch's Membrane: Implications for Age-Related Macular Degeneration

Abstract: The quantity of HS decreases substantially with age in human BrM, resulting in fewer binding sites for CFH and especially affecting the ability of the 402H variant of CFH to bind BrM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 59 publications
3
62
0
Order By: Relevance
“…Because the main binding partner for CFH in human macular BrM is heparan sulfate (55, 56) and lipoproteins interact with heparan sulfate (54), we hypothesized that CFH competes with lipoproteins for binding to HSPGs. This hypothesis is further supported by the high concentrations of HSPGs found in BrM as well as studies implicating HSPGs in AMD (55, 56, 7476). Here, we show that CFH plays a direct role in modulating the interaction between BrM and endogenous lipoprotein particles that accumulate with age in human BrM.…”
Section: Discussionmentioning
confidence: 58%
“…Because the main binding partner for CFH in human macular BrM is heparan sulfate (55, 56) and lipoproteins interact with heparan sulfate (54), we hypothesized that CFH competes with lipoproteins for binding to HSPGs. This hypothesis is further supported by the high concentrations of HSPGs found in BrM as well as studies implicating HSPGs in AMD (55, 56, 7476). Here, we show that CFH plays a direct role in modulating the interaction between BrM and endogenous lipoprotein particles that accumulate with age in human BrM.…”
Section: Discussionmentioning
confidence: 58%
“…The primary cause of AMD is not known, but several lines of investigation have been directed at elucidating the connection between BM aging and cellular changes seen in the disease, such as RPE atrophy and photoreceptor degeneration. 10,11,14,18,20 Age-related changes within BM occur several decades before cellular ones, thus suggesting that BM dysfunction can precede and may induce changes in surrounding cells. 14,15,19,20 In our system, previously developed to isolate the effects of basement membrane aging from the effects of cellular aging, we have shown that BM aging affects proper attachment and proliferation of RPE cells and increases their rate of apoptosis while decreasing the rate of phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14,18,20 Age-related changes within BM occur several decades before cellular ones, thus suggesting that BM dysfunction can precede and may induce changes in surrounding cells. 14,15,19,20 In our system, previously developed to isolate the effects of basement membrane aging from the effects of cellular aging, we have shown that BM aging affects proper attachment and proliferation of RPE cells and increases their rate of apoptosis while decreasing the rate of phagocytosis. 27,28 We have also shown that reengineering human BM can improve the attachment, survival, and proliferation of the RPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations